Herding Behavior in Nepali Stock Market: Empirical Evidences based on Investors from NEPSE - Risal, Nischal; Khatiwada, Nitesh (NCC Journal, 2019)
The research paper aims to examine the attitudinal factors influencing herding behavior in order to manage the fluctuations, bubbles, and bursts in the Nepal capital market. The descriptive and analytical research design has been adopted in the study. The qualitative data has been collected through the structured, self-administered questionnaire distributed to five hundred investors of the securities market in Nepal. The usable questionnaires have been confined to 407responses. The statistical tools mean, percentages, correlation and regression analysis has been done to process the data towards findings. As the result, the decision accuracy, age and experiences have not been found significant. The result from the analysis revealed the significant relationship of hasty decision with herd behavior.